A Triple-Band Dipole Antenna with Harmonic Suppression Capability - Hamzah, Shipun Anuar; Che Seman, Fauziahanim; Mohd Shah, Shaharil; Ramli, Khairun Nidzam; Zainal, Mohd Shamian; Md Som, Mohamad; Mustapa, Mohamad Sukri; Esa, Mazlina; Nik Abd Malik, Nik Noordini; Audah, Lukman; Abdullah, Noorsaliza (International Journal of Integrated Engineering, 2020)
This paper presents a triple-band microstrip dipole antenna with undesirable harmonic suppression capability that has a prospective to be applied in the LTE/WLAN and energy harvesting systems. The proposed antenna has three parasitic elements and a stub to suppress the harmonic of higher order modes. Initially, the antenna resonates at 0.9 GHz, 2.7 GHz and 5.4 GHz. Hence, the parasitic elements are added into each of the dipoleâ€™s arm to tune the second and third frequency band to 2.4 GHz and 5.8 GHz. However, the presence of these three parasitic elements has generated an unwanted harmonic at 4 GHz. Therefore, a stub has been connected to the terminal of the antenna to eliminate that frequency. The final design is now consists of a triple frequency bands (0.8 GHz, 2.4 GHz and 5.8 GHz) which are free from the undesirable harmonics. The corresponding measured reflection coefficients on those frequencies are -32.42 dB, -18.28 dB and -27.10 dB. The antenna is fabricated on a FR-4 printed circuit board with a relative permittivity, Îµr of 4.3, loss tangent, tan Î´ of 0.0190 and thickness, h of 1.6 mm. The overall size of the substrate of the antenna is 72 Ã— 152 mm2. The simulated and the measured results are in a good agreement, which validates the suggested antenna design.